Mechanical study of the June 2000 south Icelandic crisis based on 3D finite element models: rheological and geometrical effects - Dubois, Loïc (CCSD, 2006)
In an atypical transform zone located in the southwest of Iceland, a sequence of earthquakes (including two MW = 6.5 events) occurred in June 2000. A large amount of InSAR and GPS data covers the various phases of a seismic cycle. The use of a numerical code based on a finite-element method has allowed to analyze in each phase of the cycle the influences on the deformation of the heterogeneities which exist in the South Icelandic Seismic Zone. The coseismic deformation is especially sensitive to the increase of lithospheric stiffness with depth. The geometry of the rheological layers also has an influence during the post-seismic interval, when various related processes (visco- and poro-elastic relaxations, afterslip.) appear to occur on partially overlapping time- and length-scales. The asymmetrical distribution of stress during the inter-seismic interval due to the crustal thinning towards the west appears to be an essential factor to explain the east to west migration of seismicity. Au niveau d'une zone transformante atypique se situant au sud-ouest de l'Islande, une série de séismes majeurs (MW = 6,5) s'est produite en juin 2000. De nombreuses données InSAR et GPS couvrent les différentes phases d'un cycle sismique. L'utilisation d'un code de calcul numérique fondé sur une méthode d'éléments finis a permis d'explorer les influences sur la déformation des hétérogénéités présentes au niveau de la zone sismique sud islandaise. Dans la phase co-sismique, l'hypothèse majeure est la rigidification de la lithosphère avec la profondeur. Dans la phase post-sismique, la géométrie des couches rhéologiques a également une influence, ainsi que l'étude simultanée des différents processus associés (relaxations visco- et poro-élastique, afterslip.). Enfin, la répartition asymétrique des contraintes lors de la phase inter-sismique due à l'amincissement de la croûte vers l'ouest semble être un facteur essentiel pour expliquer la migration est-ouest observée dans la sismicité